BPPV: Comparison of the SémontPLUS With the Sémont Maneuver: A Prospective Randomized Trial - Strupp, Michael; Goldschagg, Nicolina; Vinck, Anne-Sophie; Bayer, Otmar; Vandenbroeck, Sebastian; Salerni, Lorenzo; Hennig, Anita; Obrist, Dominik; Mandalà, Marco (Frontiers in Neurology, 2021)
Objective: To compare the efficacy of the Sémont maneuver (SM) with the new “SémontPLUS maneuver” (SM+) in patients with posterior canal BPPV canalolithiasis (pcBPPVcan). Methods and Patients: In a prospective trinational (Germany, Italy, Belgium) randomized trial, patients with pcBPPVcan were randomly assigned to SM or SM+; SM+ means overextension of the head by 60+° below earth horizontal line during the movement of the patient towards the affected side. The first maneuver was done by the physician, the subsequent maneuvers by the patients on their own 9times/day. Each morning the patient documented whether vertigo could be induced. The primary endpoints were: “How long (days) does it take until no attacks can be induced?” and “What is the efficacy of a single SM/SM+?” Results: In the 194 patients analyzed (96 SM, 98 SM+), it took 2 days (median, range 1-21 days, mean 3.6 days) for recovery with SM and 1 day (median, range 1-8 days, mean 1.8 days) with SM+ (p=0.001, Mann-Whitney-u-test). There was no difference in the second primary endpoint (Chi²-test p=0.39). Interpretation: This prospective trial shows that SM+ is more effective than SM when repeated therapeutic maneuvers are performed, but not when a single maneuver is performed. It also supports the hypothesis of the biophysical model: overextension of the head during step 2 brings the clot of otoconia beyond the vertex of the canal, which increases the effectivity. Classification of Evidence: This study provides Class I evidence that SM+ is superior to SM for multiple treatment maneuvers of pcBPPVcan.